Agri-environmental policy in Germany: soil and water conservation - Peter Weingarten (Institute of Agricultural Development in Central and Eastern Europe (IAMO), 1997)
This paper is concerned with agri-environmental policy in Germany and focuses in particular on soil and water conservation. At first it discusses to what extent agriculture contributes to erosion and the pollution of surface waters and groundwater with nutrients and pesticides. Whereas erosion is a minor problem in Germany water pollution due to modern and intensive agriculture is of major concern. In theory, a broad range of environmental policy instruments exists. In practice, agri-environmental policy in Germany is dominated by command-and-control-measures, whereas incentivebased measures are of minor importance. In this paper recent developments of the most important legal and institutional settings concerning soil and water conservation policies are surveyed with special emphasis on the Federal Water Act and the Implementation of the EU Nitrate Directive into German legislation by the Fertilizer Ordinance. Since the Common Agricultural Policy (CAP) of the EU heavily affects farm structure, production intensity and regional specialization in agriculture, agri-environmental issues cannot be discussed without taking into account agricultural policy. Hence, the paper argues, that for different reasons the CAP is likely to become more environmentally friendly in future. Furthermore, impacts of alternative water conservation policies are investigated by using a regionalized agricultural sector model. Information obtained by the model analysis cover the development of nitrogen balances, potential nitrate concentrations in the soil percolation water, potentially resulting costs and effects on the agricultural incomes in the former FRG on the county level. – – Im ersten Teil dieses Beitrages über Agrarumweltpolitik in Deutschland im Bereich des Bodenund Gewässerschutzes wird ein Überblick über den landwirtschaftlich bedingten Bodenabtrag und die Belastung von Oberflächengewässern und Grundwasser mit Nährstoffen und Pflanzenschutzmitteln gegeben. Während Erosion in Deutschland von geringer Relevanz ist, kommt der durch eine moderne und intensiv betriebene Landwirtschaft verursachten Gewässerverschmutzung eine erheblich größere Bedeutung zu. In der umweltökonomischen Theorie existiert eine Reihe von umweltpolitischen Instrumenten. In der Praxis wird die Umweltpolitik in Deutschland von Ge- und Verboten geprägt, während anreizorientierte Maßnahmen nur selten eingesetzt werden. Der Artikel untersucht die wichtigsten rechtlichen und institutionellen Rahmenbedingungen im Bereich der Boden- und Gewässerschutzpolitik, wobei das Schwergewicht auf dem Wasserhaushaltsgesetz und der Düngeverordnung liegt, mit der die EU-Nitratrichtlinie in deutsches Recht umgesetzt wird. Da die Gemeinsame Agrarpolitik der EU (GAP) die Betriebsstruktur, Produktionsintensität und die regionale Spezialisierung der Landwirtschaft beeinflußt, können Agrarumweltfragen nicht diskutiert werden, ohne die Agrarpolitik zu berücksichtigen. Aus verschiedenen Gründen ist es wahrscheinlich, daß die GAP in Zukunft etwas umweltfreundlicher gestaltet wird. Mit Hilfe eines regionalisierten Agrarsektormodells werden die Auswirkungen alternativer Grundwasserschutzstrategien analysiert. Die Modellergebnisse erlauben für die alten Bundesländer Deutschlands auf der Ebene der Landkreise Aussagen über die Entwicklung von Stickstoffbilanzen, potentiellen Nitratkonzentrationen im neugebildeten Grundwasser, hierdurch potentiell hervorgerufene Kosten und Auswirkungen auf die Einkommen in der Landwirtschaft.
urn:nbn:de:gbv:3:2-22638
Keywords: 330; Agrarpolitik; Umweltpolitik; Bodenschutz; Gewässerschutz; EU-Agrarpolitik; Wirtschaftspolitische Wirkungsanalyse; Deutschland